2022
DOI: 10.1029/2022gl101014
|View full text |Cite
|
Sign up to set email alerts
|

MAVEN Proton Observations Near the Martian Moon Phobos: Does Phobos Backscatter Solar Wind Protons?

Abstract: Backscattering of solar wind ions by a planetary surface is a fundamental process that may occur at all bodies exposed to the solar wind and unprotected by a thick atmosphere, that is, the Moon, Mercury, the moons of Mars, dwarf planets, asteroids, and comets. The overarching questions at stake include: (a) what are the key parameters that control the efficiency and angular distribution of solar wind ion backscattering, including solar wind parameters (density, bulk speed, temperature, composition) and surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The surface of comet 67P, and potentially cometary surfaces in general, seems to interact differently with the surrounding A245, page 8 of 13 Canu-Blot, R., et al: A&A, 683, A245 (2024) Deniau et al (2022) reported no evidence of backscattered solar wind H + from Phobos. An upper limit of the differential directional energy flux is given as 10 6 eV cm −2 s −1 sr −1 eV −1 .…”
Section: Reasons For a Truly Small Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface of comet 67P, and potentially cometary surfaces in general, seems to interact differently with the surrounding A245, page 8 of 13 Canu-Blot, R., et al: A&A, 683, A245 (2024) Deniau et al (2022) reported no evidence of backscattered solar wind H + from Phobos. An upper limit of the differential directional energy flux is given as 10 6 eV cm −2 s −1 sr −1 eV −1 .…”
Section: Reasons For a Truly Small Signalmentioning
confidence: 99%
“…Additionally, measurements by Mars Express suggested that 0.5-10% of solar wind H + backscatter from the regolithcovered surface of Phobos (Futaana et al 2010), but subsequent measurements from MAVEN were unable to reproduce this result (Deniau et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While so far only extensively observed at the Moon, similar ion backscattering processes can be assumed to occur at other atmosphereless bodies in the solar system. Measurements of backscattered protons from the Martian Moon Phobos have been attempted with the Mars Express and MAVEN spacecraft (Deniau et al, 2022;Futaana et al, 2010Futaana et al, , 2021, leading to inconclusive results. Low fluxes of reflected charged particles, electromagnetic fields that affect ion paths, and the Martian hydrogen exosphere as a potential additional source of protons complicate the observation.…”
mentioning
confidence: 99%